The projected timeframe until cervical cancer elimination in Australia: a modelling study - Michaela T Hall, MMath; Kate T Simms, PhD; Jie-Bin Lew, PhD; Megan A Smith, PhD; Julia ML Brotherton, PhD; Marion Saville, MBChB; Ian H Frazer, ProfDSc; Karen Canfell, ProfDPhil (Elsevier, 2019)
Summary: Background: In 2007, Australia was one of the first countries to introduce a national human papillomavirus (HPV) vaccination programme, and it has since achieved high vaccination coverage across both sexes. In December, 2017, organised cervical screening in Australia transitioned from cytology-based screening every 2 years for women aged from 18-20 years to 69 years, to primary HPV testing every 5 years for women aged 25-69 years and exit testing for women aged 70-74 years. We aimed to identify the earliest years in which the annual age-standardised incidence of cervical cancer in Australia (which is currently seven cases per 100 000 women) could decrease below two annual thresholds that could be considered to be potential elimination thresholds: a rare cancer threshold (six new cases per 100 000 women) or a lower threshold (four new cases per 100 000 women), since Australia is likely to be one of the first countries to reach these benchmarks. Methods: In this modelling study, we used Policy1-Cervix-an extensively validated dynamic model of HPV vaccination, natural history, and cervical screening-to estimate the age-standardised incidence of cervical cancer in Australia from 2015 to 2100. We incorporated age-specific coverage of the Australian National HPV Vaccination Program in girls, including the catch-up programme, and the inclusion of boys into the vaccine programme from 2013, and a change from the quadrivalent to the nonavalent vaccine from 2018. We also modelled the effects of the transition to primary HPV screening. We considered two scenarios for future screening recommendations regarding the cohorts who will be and who have been offered the nonavalent vaccine: either that HPV screening every 5 years continues, or that no screening would be offered to these women. Findings: We estimate that, in Australia, the age-standardised annual incidence of cervical cancer will decrease to fewer than six new cases per 100 000 women by 2020 (range 2018-22), and to fewer than four new cases per 100 000 women by 2028 (2021-35). The precise year of attaining these rates is dependent on the population used for age-standardisation, HPV screening behaviour and test characteristics, the incremental effects of vaccination of men on herd immunity in women, and assumptions about the future frequency of benign hysterectomies. By 2066 (2054-77), the annual incidence of cervical cancer will decrease and remain at fewer than one case per 100 000 women if screening for HPV every 5 years continues for cohorts who have been offered the nonavalent vaccine, or fewer than three cases per 100 000 women if these cohorts are not screened. Cervical cancer mortality is estimated to decrease to less than an age-standardised annual rate of one death per 100 000 women by 2034 (2025-47), even if future screening is only offered to older cohorts that were not offered the nonavalent vaccine. Interpretation: If high-coverage vaccination and screening is maintained, at an elimination threshold of four new cases per 100 000 women annually, cervical cancer could be considered to be eliminated as a public health problem in Australia within the next 20 years. However, screening and vaccination initiatives would need to be maintained thereafter to maintain very low cervical cancer incidence and mortality rates. Funding: National Health and Medical Research Council (Australia).